Performance appraisal purposes in Kwara State Civil Service, Nigeria: analysis of employee engagement and performance. - Ameen, Lateef (2020)
The existing study in the administration research field signifies that employee engagement and employee performance are crucial to the effectiveness of civil service. This is due to the fact that organizational performance and success significantly hinge on both of the factors. However, very slight consideration has been given to the relationship between performance appraisal purposes (PAP) and employee engagement as well as employee performance in the context of civil service. The main aim of this research is to examine the relationship between PAP (training, job promotion, performance feedback, performance recognition and financial reward) and engagement and performance of civil servants in Kwara State Civil Service, Nigeria.To validate the instruments employed in this study, seven (7) experts were consulted for content validation of the adapted scales before a pilot study was conducted among 100 respondents. Subsequently, a total number of 510 civil servants were involved in this study. Data for the study were gathered through quantitative and qualitative surveys from employees working in the Kwara State civil service. PLS-SEM was used to test the study’s hypotheses. The results provided support for six (6) out of the eleven (11) hypotheses. The overall findings signify that job promotion, performance recognition and financial reward have a significant positive relationship with employee engagement, while training and performance feedback have insignificant relationship with employee engagement.The results also indicated that training and financial reward have a significant and positive relationship with employee performance, while the job promotion, performance feedback and performance recognition have insignificant relationships with employee performance. Moreover, the results reveal a significant relationship between employee engagement and employee performance. Consequently, this study successfully provides empirical evidence to the practitioners on employee engagement and performance. It also provides insights for civil service directors on how to enhance employee engagement and performance via training, promotion, feedback, recognition and financial reward.